On Reduced and Semicommutative Modules - Başer, Muhittin; Agayev, Nazım (TÜBİTAK, 2006)
In this paper, various results of reduced and semicommutative rings are extended to reduced and semicommutative modules. In particular, we show: (1) For a principally quasi-Baer module, MR is semicommutative if and only if MR is reduced. (2) If MR is a p.p.-module then MR is nonsingular.
Keywords: Reduced Rings (Modules); Baer, quasi-Baer and Rings (Modules)